Proportion of patients with hip osteoarthritis in primary care identified by differing clinical criteria: a cross-sectional study of 4699 patients - James J. Young; Søren T. Skou; Bart W. Koes; Dorte T. Grønne; Ewa M. Roos (Osteoarthritis and Cartilage Open, 2020)
Summary: Objective: Differing clinical criteria for hip osteoarthritis (OA) are applied in primary care, but little is known regarding the utility of these criteria. The aim of this study was to evaluate and compare the proportion of patients in a primary care setting with hip OA fulfilling the American College of Rheumatology (ACR), the National Institute for Health and Care Excellence (NICE), and the Danish Health Authority (DHA) criteria. Design: A cross-sectional analysis of baseline data from the Good Life with osteoArthritis in Denmark (GLA:D®) program, a treatment program for patients with symptoms or functional limitations associated with hip OA. The prevalence of hip OA according to the ACR, NICE, and DHA criteria was calculated in all patients and in a subgroup of patients with self-reported radiographic hip OA. Results: 4699 patients were included in the analysis. Mean age (SD) was 66.8 (9.7) years and 71% of the patients were female. 64%, 80%, and 94% fulfilled the ACR, DHA, and NICE criteria, respectively. In those self-reporting radiographic hip OA, the corresponding numbers were 66%, 81%, and 94%. A limited number of patients (4%) did not fulfill any of the criteria. Conclusions: The NICE criteria identified the most patients that were treated because of their symptoms or functional limitations. The DHA and especially the ACR criteria did not identify a significant proportion of these patients. The results suggest the NICE criteria are appropriate to identify individuals treated for hip OA in primary care.